2017
DOI: 10.22260/isarc2017/0011
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Low Cost Capacitive ECG via Arduino and Single-Board Computer Interfaced with Capacitive Electrodes for Prevention and Security Aspects

Abstract: Coronary heart disease (CHD), and its different variants, is one of the major reasons of increased death rates in industrialized nations. As the beginning of the disease is symptom free, unconsciousness and sudden death, as well as health related distortions can trigger accidents at construction sites any time. Therefore, there is a need for systems, which can detect such silent symptoms, in order to prevent health related accidents on construction site. Nowadays, most common way to identify first symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The mechanism of the DRL circuit is to suppress the common-mode noise from the power line using the reference electrode. The common-mode voltage can be expressed as (15); therefore, the common-mode noise can be reduced by a factor of 1+(2R f /R a ) [23]. The common-mode noise can be reduced by an amplification factor of 201, according (16):…”
Section: Hardware Designmentioning
confidence: 99%
“…The mechanism of the DRL circuit is to suppress the common-mode noise from the power line using the reference electrode. The common-mode voltage can be expressed as (15); therefore, the common-mode noise can be reduced by a factor of 1+(2R f /R a ) [23]. The common-mode noise can be reduced by an amplification factor of 201, according (16):…”
Section: Hardware Designmentioning
confidence: 99%
“…These challenges result in part from the dynamic work environments of construction, the frequent use of heavy equipment, and the unavoidable worker-hazard interactions (Hallowell and Gambatese, 2009). As part of efforts to improve construction safety performance, researchers have reported that the application of safety technologies within various phases of construction projects will significantly enhance the safety and health of construction workers (Ahuja et al, 2010;Guo et al, 2017;Güttler and Bock, 2017;Nnaji et al, 2019). Of these technologies, wearable sensing devices (WSDs) have been gaining a lot of attention in the construction industry in recent times (Awolusi et al, 2018;Nnaji and Karakhan, 2020;SmartMarket Report, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefits of WSDs for personalized safety have been extensively covered in safety research (Ahn et al, 2019;Awolusi et al, 2018;Jebelli et al, 2019a). Although WSDs have the potential to significantly reduce accidents and the attendant losses associated with accidents (Güttler and Bock, 2017;Jebelli et al, 2019a;Okpala et al, 2020;Pehr et al, 2020), this reduction is only possible when workers truly perceive WSDs utility and decide to use the device during work. WSDs acceptance at an individual level fosters widespread integration across an organization (Khakurel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Growing presence of wireless networks also justifies the realization of wearable ECG devices that forward the ECG trace to a nearby communication device. Bluetooth and ZigBee [29][30][31] are the two main low power wireless transmission technologies used in ECG wireless monitoring systems. ZigBee is an open global standard protocol designed for use with wireless personal area networks (WPANs).…”
Section: Introductionmentioning
confidence: 99%